Lack of β2-AR Increases Anxiety-Like Behaviors and Rewarding Properties of Cocaine - Zhu, Huiwen; Liu, Zhiyuan; Zhou, Yiming; Yin, Xuming; Xu, Bo; Ma, Lan; Liu, Xing (Frontiers in Behavioral Neuroscience, 2017)
It is well known that β-adrenoceptors (β-ARs) play a critical role in emotional arousal and stressful events, but the specific contributions of the β2-AR subtype to the psychological disorders are largely unknown. To investigate whether β2-AR are involved in anxiety-like behavior and reward to addictive drugs, we conducted a series of behavioral tests on β2-AR knock-out (KO) mice. β2-AR KO mice exhibited increased preference for the dark compartment and closed arm in tests of Light/Dark box and elevated plus maze, indicating that β2-AR deletion elevates level of anxiety or innate fear. β2-AR KO mice also showed decreased immobility in tail suspension test, suggesting that β2-AR deletion inhibits depression-like behavior. Interestingly, β2-AR ablation did not change basal locomotion but significantly increased locomotor activity induced by acute cocaine administration. β2-AR KO mice showed enhanced place preference for cocaine, which could be attenuated by β1-selective AR antagonist betaxolol. Consistently, β2-AR agonist suppressed cocaine-conditioned place preference. These data indicate that β2-AR deletion enhances acute response and reward to cocaine. Our results suggest that β2-AR regulates anxiety level, depression-like behavior and hedonic properties of cocaine, implicating that β2-AR are the potential targets for the treatment of emotional disorders and cocaine addiction.